Application of Taguchi Method to analyze the impacts of commonality in multistage production under uncertainty - Wazed, M.A.; Ahmed, S.; Nukman, Y. (2011)
The work explores the optimum level of batch size in bottleneck facility and the effect of common components on work-in-process (WIP) level and cycle time in a multistage production system in an uncertain environment created by machine breakdown and quality variation. Few simulation models are developed based on a live case from a company. The models are verified and validated with the historical data from the company and by face validity. Taguchi approaches for orthogonal array are used in designing experiments and these are executed in WITNESS, a simulation package. It is observed that the variation in level of common component in the system has a significant impact on the production WIP level and cycle time. The main contribution of this research is the determination of the optimal level of batch size in a bottleneck resource under the uncertainties. This approach can be generalized to any multistage production system, regardless of the precedence relationships among the various production stages in the system.